The Analysis of Use Register for Computer System Based on English For Specific Purpose (ESP) Theories at Vocational High School Al-Huda Sumber Nangka Pamekasan - Siti Mukamilah; Ary Iswahyudi (Wacana Didaktika, 2018)
English has a more specific coverage, it is known as "English for specific Purpose (ESP)" which the developed of scientific study is a special vocabulary used in accordance of speciefic majors such as: English for Machine, English for Religion, English for Engineering, English for Education and English for Computer. Students, teachers and lecturers can develop, apply and use English easily and can quickly understand English text more quickly by implementing ESP theories. Likewise for the English language is used in general in various educational institutions at vocational High School Al-Huda Sumber Nangka Duko Timur Pamekasan. One of material is register for computer system based become the main focusing problem that must be overcome by the teacher of improving English teachers’ profesionalism and mastered the usage of coverage ESP. This research want to analyze the use of ESP theories by using qualitative method by Miles and Huberman model analysis of data collection, data reduction, data display and verification. English for specific purpose (ESP) theories have a contibution at the practicing register for computer system for students to comprehend English material at computer specification practice. Keywords: Improvemet of ESP, Register for Computer System, English Reading Comprehension Abstrak: Bahasa Inggris memiliki cakupan yang lebih spesifik (ESP)" yang dikembangkan dari studi ilmiah adalah kosakata khusus yang digunakan sesuai jurusan seperti: Bahasa Inggris untuk Mesin, Bahasa Inggris untuk Agama, Bahasa Inggris untuk Teknik, Bahasa Inggris untuk Teknik , Bahasa Inggris untuk Pendidikan dan Bahasa Inggris untuk Komputer. Siswa, guru dan dosen dapat mengembangkan, menerapkan, dan menggunakan bahasa Inggris dengan mudah dan dapat dengan cepat memahami teks bahasa Inggris lebih cepat dengan menerapkan teori ESP. Demikian juga untuk bahasa Inggris digunakan secara umum di berbagai lembaga pendidikan di sekolah menengah kejuruan Al-Huda Sumber Nangka Duko Timur Pamekasan. Salah satu materi adalah sistem komputer berbasis menjadi masalah fokus utama yang harus diatasi oleh guru, meningkatkan profesionalisme guru bahasa Inggris dan menguasai penggunaan cakupan ESP. Penelitian ini ingin menganalisis penggunaan teori ESP dengan menggunakan metode kualitatif oleh Miles dan Huberman model analisis pengumpulan data, reduksi data, tampilan data dan verifikasi. Teori Bahasa Inggris untuk Tujuan Khusus (ESP) memiliki kontibusi pada daftar praktik sistem komputer bagi siswa untuk memahami materi bahasa Inggris di praktik spesifikasi komputer.